Disparitas Pertumbuhan Ekonomi Jawa dengan Luar Jawa - Ardito Bhinadi (Economic Journal of Emerging Markets, 2003)
The background of this study was an unbalanced dynamic space of Indonesian de¬velopment. The cross-region development showed that the region in Java, in general, de¬vel¬oped faster than in the others. The differences of cross-region growth, Java and out of Java impacted to a gap of wealth and developing cross-region. The purpose of this study was to estimate sources of regional growth between Java with the other regions, and to analyze regional disparity between Java with the other regions. The data used in this study was an¬nual data. The variables used in this study are per capita GRDP growth at constant prices (Y), capital growth (K), labor growth (L) and human capital growth (E). The model of regional economic growth was estimated with panel data. T-test and F-test were used to analyze dis¬parity of income growth. General conclusion of this study was the fact that significantly capital growth (K) influent regional economic growth. But, labor growth (L) and human capital growth (E) were not. The outcomes of statistic test showed that there was not re¬gional growth disparity. Key words: sources of growth, growth disparit.